The Golgi microtubules regulate single cell durotaxis. (9th February 2021) - Rong, Yingxue; Yang, Wenzhong; Hao, Huiwen; Wang, Wenxu; Lin, Shaozhen; Shi, Peng; Huang, Yuxing; Li, Bo; Sun, Yujie; Liu, Zheng; Wu, Congying
Abstract: Current understandings on cell motility and directionality rely heavily on accumulated investigations of the adhesion–actin cytoskeleton–actomyosin contractility cycles, while microtubules have been understudied in this context. Durotaxis, the ability of cells to migrate up gradients of substrate stiffness, plays a critical part in development and disease. Here, we identify the pivotal role of Golgi microtubules in durotactic migration of single cells. Using high‐throughput analysis of microtubule plus ends/focal adhesion interactions, we uncover that these non‐centrosomal microtubules actively impart leading edge focal adhesion (FA) dynamics. Furthermore, we designed a new system where islands of higher stiffness were patterned within RGD peptide coated polyacrylamide gels. We revealed that the positioning of the Golgi apparatus is responsive to external mechanical cues and that the Golgi–nucleus axis aligns with the stiffness gradient in durotaxis. Together, our work unveils the cytoskeletal underpinning for single cell durotaxis. We propose a model in which the Golgi–nucleus axis serves both as a compass and as a steering wheel for durotactic migration, dictating cell directionality through the interaction between non‐centrosomal microtubules and the FA dynamics. SYNOPSIS: The Golgi‐nucleus axis serves both as a compass and a steering wheel for durotactic migration, dictating cell directionality through the interaction between non‐centrosomal microtubules and the FA dynamics. Loss of the Golgi microtubules impairs durotaxis. Loss of the Golgi microtubules does not affect RhoA activity or cell contraction. Loss of the Golgi microtubules alters focal adhesion dynamics. The Golgi apparatus is oriented in response to mechanical cues and maintains cell polarity. Abstract : The Golgi‐nucleus axis serves both as a compass and a steering wheel for durotactic migration, dictating cell directionality through the interaction between non‐centrosomal microtubules and the FA dynamics.